A Phosphorylation‐Induced Turn Defines the Alzheimer's Disease AT8 Antibody Epitope on the Tau Protein1. Issue 23 (16th April 2015) - Gandhi, Neha S.; Landrieu, Isabelle; Byrne, Cillian; Kukic, Predrag; Amniai, Laziza; Cantrelle, François‐Xavier; Wieruszeski, Jean‐Michel; Mancera, Ricardo L.; Jacquot, Yves; Lippens, Guy
Abstract: Post mortem biochemical staging of Alzheimer's disease is currently based on immunochemical analysis of brain slices with the AT8 antibody. The epitope of AT8 is described around the pSer202 /pThr205 region of the hyperphosphorylated form of the neuronal protein tau. In this study, NMR spectroscopy was used to precisely map the AT8 epitope on phosphorylated tau, and derive its defining structural features by a combination of NMR analyses and molecular dynamics. A particular turn conformation is stabilized by a hydrogen bond of the phosphorylated Thr205 residue to the amide proton of Gly207, and is further stabilized by the two Arg residues opposing the pSer202 /pThr205 . Abstract : The AT8 epitope of the phosphorylated tau protein was mapped by NMR spectroscopy, and its defining structural features were derived by a combination of NMR analyses and molecular dynamics. A particular turn conformation is stabilized by a hydrogen bond of the phosphorylated Thr205 residue (pThr205 ) to the amide proton of Gly207 .